2019
DOI: 10.1111/jipb.12785
|View full text |Cite
|
Sign up to set email alerts
|

A strategy for generating rice apomixis by gene editing

Abstract: Summary Apomixis is an asexual reproduction way of plants that can produce clonal offspring through seeds. In this study, we introduced apomixis into rice (Oryza sativa) by mutating OsSPO11‐1, OsREC8, OsOSD1, and OsMATL through a CRISPR/Cas9 system. The quadruple mutant showed a transformation from meiosis to mitosis and produced clonal diploid gametes. With mutated Osmatl, which gives rise to haploid induction in plants, the quadruple mutant is expected to be able to be produced apomictic diploid offspring. W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(25 citation statements)
references
References 16 publications
0
25
0
Order By: Relevance
“…Recently, using CRISPR-Cas9, some researchers attempted to set up synthetic apomixis in rice but a maximum of 29% of offspring were maternal clones [80][81][82]. Here we have demonstrated that PpAPOSTART is expressed in different cells (MMC vs. Nucellar), and for one of its members (APOSTART_6), the expression is delayed confirming the hypothesis that the shift in timing and place of expression may cause apomixis or, at least, one of the two components of apomictic development.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, using CRISPR-Cas9, some researchers attempted to set up synthetic apomixis in rice but a maximum of 29% of offspring were maternal clones [80][81][82]. Here we have demonstrated that PpAPOSTART is expressed in different cells (MMC vs. Nucellar), and for one of its members (APOSTART_6), the expression is delayed confirming the hypothesis that the shift in timing and place of expression may cause apomixis or, at least, one of the two components of apomictic development.…”
Section: Discussionmentioning
confidence: 99%
“…The quadruple AOP (Apomictic Offspring Producer) mutants obtained through the knockout of OsSPO11-1, OsREC8, OsOSD1 and OsMATL produced the MiMe phenotype. The mutant has the ability to produce apomictic plants [20]. However, thus far, the number of viable clone seeds with their original hybrid genetics intact are much lower than expected and this area needs further research.…”
Section: Synthetic Apomixis Through Genome Editing To Preserve Hybridmentioning
confidence: 99%
“…Wang et al [16] introduced synthetic apomixis in few fruit crops i.e., citrus and apple however, the epigenetic modifications involvements caused severe seed abortion leading toward the failure in transfer of apomixis in major crops [10]. Recent studies have discussed the genetics and biotechnology approaches [17], integration of knowledge from various aspect of plant breeding [18], and methods for exploiting genome editing, especially CRISPR/Cas genome editing system for improving yield and preservation of heterosis in hybrids [19,20]. The scientific community equipped with genome editing expertise has played its significant role by transferring relevant and reliable information to beginners in genome editing, on contrary to the proprietary nature of zinc-finger nucleases (ZFNs).…”
Section: Introductionmentioning
confidence: 99%
“…Among the 145 collected seeds, 9 proved to be diploid, heterozygous and apomictic, while the remaining seeds were tetraploids and nonapomictic. This MiMe/matl quadruple mutation strategy has been also been recently implemented using Osspo11‐1 rather than pair1 for abolishing homologous chromosome pairing and recombination, thereby reproducing the original Arabidopsis MiMe mutant composition (Xie et al , ). Unless enhanced phenotypic penetrance from the current 5%–6% haploid seed induction frequency is obtained by further manipulation of OsMATL , it is unlikely that this strategy will allow the 100% apomictic seed production that is needed for clonal reproduction of F1 hybrids.…”
Section: Abolishing Meiotic Recombination To Engineer Apomixismentioning
confidence: 99%